Intercropping in high input agriculture supports arthropod diversity without risking significant yield losses - Brandmeier, Jana; Reininghaus, Hannah; Pappagallo, Silvia; Karley, Alison J.; Kiær, Lars P.; Scherber, Christoph (Basic and applied ecology, 2021)
•Increased crop diversity and reduced management intensity promote arthropods.•Pollinators and natural enemies, but not all herbivores, benefit from intercropping.•Mostly, total grain yield is higher in mixtures than in monocultures.•Intercropping can obtain high yields and increase arthropod abundance and diversity. Arthropod diversity of different taxonomic groups and ecosystem services are declining, yet current measures to counteract losses are often restricted to small areas of land or field margins, particularly in agricultural systems. At the same time, large areas of land will be required to feed a growing global population. Intercropping has been proposed as a potential solution to maximize both biodiversity and yield at large scale, but experimental evidence is scarce. In a three-year field experiment, we manipulated crop diversity and management intensity in a cereal-legume intercropping experiment in Germany, where 50% of wheat was replaced by faba beans. We measured arthropod abundance and diversity of different functional groups (pollinators, natural enemies, herbivores) and crop yield. We found that increasing crop diversity increased abundance and diversity of arthropods. Notably, pollinator and natural enemy abundances increased in intercropped systems. Low management intensity generally had positive effects on arthropod abundance and especially on pollinator diversity, indicating benefits of reduced inputs of fertilizers and herbicides. While wheat yield was higher in monocultures and for high management intensity, total grain yield of the intercrop (indicated by land equivalent ratio) was higher in mixtures. We found that trade-offs were stronger between arthropod diversity and wheat yield than between arthropod abundance and wheat yield. Specialist wheat herbivores and generalist herbivores were more abundant at higher wheat yields. Conversely, pollinator and natural enemy diversity were negatively associated with wheat yield. Our results show that diversification can promote both higher yields and greater diversity of arthropods. Intercropping can thus be an opportunity to support biodiversity without risking significant yield losses.